2004
DOI: 10.1177/0891988704267456
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Parkinson’s Disease: Conceptual Issues and Clinical Challenges

Abstract: Background: Depression frequently accompanies Parkinson’s disease (PD) and may have a negative impact on activities of daily living, cognitive performance, and quality of life. Because of the symptom overlap between the 2 disorders, it may be difficult to recognize depression in PD. Moreover, the partially shared pathophysiology may make it difficult to treat depressive symptoms without influencing motor or cognitive function. Objective: To review the current knowledge of the epidemiology, etiology, pathophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
0
8

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 76 publications
4
83
0
8
Order By: Relevance
“…If the two disorders have similar risk factors or neurobiological underpinnings, the co-occurrence of psychosis and depression would be greater than expected by chance alone, and previous research suggests that there may be an association between the two disorders [4][5][6][7]. If so, this may be due to common risk factors, including increasing age [6,8], greater cognitive impairment [4,9], and greater PD severity [6,9]. Other purported risk factors for individual disorders include exposure to most dopaminergic therapies (psychosis) [10], and female sex, predominantly right-sided motor symptoms, and treatment with higher levodopa doses (depression) [9,11,12].…”
Section: Introductionmentioning
confidence: 97%
“…If the two disorders have similar risk factors or neurobiological underpinnings, the co-occurrence of psychosis and depression would be greater than expected by chance alone, and previous research suggests that there may be an association between the two disorders [4][5][6][7]. If so, this may be due to common risk factors, including increasing age [6,8], greater cognitive impairment [4,9], and greater PD severity [6,9]. Other purported risk factors for individual disorders include exposure to most dopaminergic therapies (psychosis) [10], and female sex, predominantly right-sided motor symptoms, and treatment with higher levodopa doses (depression) [9,11,12].…”
Section: Introductionmentioning
confidence: 97%
“…Although there are attractive alternative hypotheses about the role of serotonin in PD, this hypothesis is appealing because it provides an explanation for some common clinical observations. The presence of this biological risk factor for depression may explain the high prevalence of this condition in patients with PD (Leentjens, 2004). It may also explain the increased incidence of depression preceding the diagnosis of PD, because of the fact that pathophysiological compensatory mechanisms are already in action long before clinical symptoms become apparent (Leentjens et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Mood disturbance, and especially major depressive disorder, is a common condition in Parkinson's disease (PD), with an average prevalence of 25-40% in outpatient settings (Leentjens, 2004). Depression is associated with a reduced quality of life, increased functional disability, more severe cognitive symptoms, and enhanced caregiver's stress (Troster et al, 1995;Liu et al, 1997;Aarsland, 1999;Hobson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been suggested that the reduced DA activity in PD can lead, as physiological adaptation, to a reduction of serotonergic tone and, at the same time, constitute a risk factor for depression (Mayeux, 1990). The presence of this biological risk factor for depression may explain the high prevalence of this condition in patients with PD (Leentjens, 2004). Nevertheless, a recent double-blind, randomized study provided no support for the serotonergic hypothesis of depression in PD, using the acute tryptophan depletion (ATD) paradigm .…”
Section: Role Of 5-ht In Psychiatric Complications In Pdmentioning
confidence: 99%
“…Mood disturbance, and especially major depressive disorder, has an average prevalence of 25-40% in outpatient settings (Leentjens, 2004;Veazey et al, 2005;Miller et al, 2007). According to the serotonergic hypothesis of depression in PD (Mayeux, 1990), 5-HT seems to play a central role.…”
Section: Role Of 5-ht In Psychiatric Complications In Pdmentioning
confidence: 99%